Successive surgical repair of a progressive aortic dissection in a case of Loeys–Dietz Syndrome - Pathare, Presheet; Elbayomi, Mohamed; Tandler, Rene; Weyand, Michael; Harig, Frank (Journal of Cardiac Surgery, 2022)
Introduction: The Frozen Elephant Trunk technique is a well-established treatment for aortic dissections (Stanford Type A) involving the aortic arch and descending aorta. The Thoraflex™ Hybrid prosthesis (Vascutek Ltd.), consisting of a proximal flexible conduit and a distal self-expanding covered stent, has consistently shown positive results in the treatment of this condition. Case Description: The following is a description of such a staged reconstruction using the Thoraflex™ Hybrid Ante-Flo™ device, performed in a patient previously diagnosed with Loeys–Dietz Syndrome. After clamping the aorta proximally, an incision was taken at the distal end of the stent. Here, the distal end of the new prosthesis was inserted into the true lumen of the descending aorta and the stent was deployed. Following this, a bypass was established via the left atrium, and blood was returned to the lower body using the perfusion arm of the prosthesis with the proximal part of the descending aorta clamped. The collar of the prosthesis was sutured proximally to the aorta near the inlying previous stent. Air was removed via the perfusion arm of the prosthesis, which was then oversewn. Discussion: To date, hybrid prostheses have only been used on the proximal aorta in patients with aortic aneurysms and aortic dissections (Stanford Type A). Conclusion: Using the described technique, it is possible to reconstruct the aortic anatomy using the available prostheses with accuracy and minimal complications.
CRIS-Team Scopus Importer:2022-12-02
Keywords: aorta and great vessels; perfusion